Diversity and utilization of vegetables and spices by coastal community in East Aceh, Indonesia - NURSAMSU NURSAMSU; ENDANG SUSANTINI; YULIANI YULIANI; NURHAFIDHAH NURHAFIDHAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Nursamsu, Susantini E, Yuliani, Nurhafidhah. 2025. Diversity and utilization of vegetables and spices by coastal community in East Aceh, Indonesia. Biodiversitas 26: 837-850. Food security a major concern in many countries, particularly in coastal regions potentially impacted by climate change and natural hazards. Food security correlates with the loss of traditional culinary expertise, particularly among the younger generation. Therefore, this research aimed to explore and document traditional knowledge about various plants used as vegetables and spice by a coastal community in East Aceh District, Aceh Province, Indonesia. Ethnobotanical knowledge data was collected in five villages using field surveys and semi-structured interviews. A total of 92 plant taxa from 41 families are used as vegetables and spices by coastal community in East Aceh, emphasizing their importance in traditional food and local culture. The Cucurbitaceae family is the family with the largest use, comprising 10 taxa which show high protein and dietary fiber content. Cocos nucifera and Nypa fruticans have the greatest Use Value (UV), with C. nucifera ranking first on the Index of Cultural Significance (ICS). Furthermore, the vegetables and spices are collected from cultivated plants (77.2%) and those grow wild (22.8%), showing a relatively high community dependence on natural ecosystem. The most widely used plant parts are fruits (42.5%) and leaves (25.7%). In conclusion, this research showed the importance of plants for food security, health, and cultural preservation, with sustainable methods such as agroecology to ensure their continuing use.